Comparison of surgical complications after curative surgery in patients with oral cavity squamous cell carcinoma and sarcopenia. Issue 1 (23rd December 2022) - Zeng, Shuang; Chang, Chia‐Hao; Sun, Mingyang; Chen, Wan‐Ming; Wu, Szu‐Yuan; Zhang, Jiaqiang
Abstract: Background: The study aims to clarify the association of sarcopenia with perioperative and postoperative complications in oral cavity squamous cell carcinoma (OCSCC) patients undergoing curative surgery and to understand the reasons causing the poor oncologic outcomes for OCSCC. Methods: We conducted a propensity score matching study to investigate the association of perioperative and postoperative outcomes in OCSCC patients with sarcopenia and without sarcopenia. A retrospective analysis of a large national data set from the Taiwan Cancer Registry Database was conducted. At least two claims for patients with a principal diagnosis of sarcopenia within the 12‐month preoperative period were defined as the criteria for sarcopenia diagnosis (ICD‐10‐CM code M62.84). Sarcopenia was diagnosed through the measurement of low muscle strength and low muscle mass by any one of the patient's attending orthopaedic physician, rehabilitation physician, family medicine specialist or geriatrician. A multivariate logistic regression model was used to calculate the perioperative, and postoperative major complications. Results: Our final cohort included 16 293 patients with OCSCC (10 862 and 5 431 in the sarcopenia and nonsarcopenia groups, respectively) who were eligible for further analysis. The sarcopenia group was 10.40% female and 89.60% male, and the nonsarcopenia group was 9.74% female and 90.26% male. The mean age ± standard deviation ( SD ) were 56.44 ± 11.14 and 56.22 ± 11.29 for sarcopenia and nonsarcopenia groups. OCSCC patients with sarcopenia undergoing curative surgery had a significantly higher blood transfusion rate and volume; longer intensive care unit (ICU) stay, and hospital stay; higher postoperative 30‐day mortality (adjusted odds ratio [aOR]: 1.12, 95% confidence interval [CI] [1.07, 1.56]) and rates of pneumonia (aOR: 1.34, 95% CI [1.20, 1.50]), acute renal failure (aOR: 1.45, 95% CI [1.12, 1.87]) and septicaemia (aOR: 1.29, 95% CI [1.15, 1.45]); higher postoperative first‐year mortality (aOR: 1.18, 95% CI [1.13, 1.51]) and rates of pneumonia (aOR: 1.43, 95% CI [1.30, 1.56]), acute myocardial infarction (aOR: 1.52, 95% CI [1.06, 2.18]) and septicaemia (aOR: 1.29, 95% CI [1.15, 1.45]). Conclusions: OCSCC patients with sarcopenia might exhibit more perioperative and surgical complications than those without sarcopenia.